2018
DOI: 10.1016/j.thromres.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of fibrinogen as a consequence of cirrhosis

Abstract: Cirrhosis is a disease which may develop as a consequence of various conditions. In advanced liver disease, blood coagulation can be seriously affected. Portal hypertension, vascular abnormalities and/or a dysbalance in coagulation factors may result in bleeding disorders or in the development of thrombosis. Fibrinogen is the main protein involved in clot formation and wound healing. The aim of this work was to analyse the glycosylation pattern of the isolated fibrinogen molecules by lectin-based protein micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…(61) This could be due to underlying inflammation, as fibrinogen is an acute-phase protein. (64,65) Fibrinogen could also undergo structural modifications, leading to functional alterations in LC. (66) One cause of thrombin time prolongation in LC is an impaired polymerization of fibrin monomers.…”
Section: Fibrinogenmentioning
confidence: 99%
See 2 more Smart Citations
“…(61) This could be due to underlying inflammation, as fibrinogen is an acute-phase protein. (64,65) Fibrinogen could also undergo structural modifications, leading to functional alterations in LC. (66) One cause of thrombin time prolongation in LC is an impaired polymerization of fibrin monomers.…”
Section: Fibrinogenmentioning
confidence: 99%
“…(66) One cause of thrombin time prolongation in LC is an impaired polymerization of fibrin monomers. (67) Several studies have reported increased sialic acid (SA) content of fibrinogen in LC (64,67) and a correlation between increased SA content of fibrinogen and prolonged thrombin time. (68) A possible explanation for the increased SA content of fibrinogen is an enhanced sialyl-transferase activity.…”
Section: Fibrinogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins were resolved by the native PAGE using 8 % gel and transferred on the poly(vinylidene fluoride) membrane (PVDF). Protein carbonyls were derivatised in situ using dinitrophenylhydrazine (DNP) and immunoblotted using anti-DNP antibody [17,18].…”
Section: Investigation Of the Protective Effect Of Bilirubin Against mentioning
confidence: 99%
“…Altered glycosylation affects fibrinogen properties in hepatic diseases [ 9 , 10 ] and the present study aimed to examine fibrinogen glycosylation in patients with ESRD-PD, as that may help in better understanding of the mechanisms underlying fibrinogen-related changes, and possibly assist in the therapeutic approach. Lectin-based protein microarray and lectin blotting were applied to define glycan structures on fibrinogen.…”
Section: Introductionmentioning
confidence: 99%